PERCEPATAN WAKTU PROYEK PEMBANGUNAN GEDUNG KEMASAN JUMBO PT SEMEN INDONESIA DENGAN METODE CRASHING - Sugiyanto Sugiyanto; Ahmad Nur Puniadi (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
In implementing accelerated construction projects, one strategy can be applied the crashing method. This study aims to analyze the cost and time of the construction project for constructing a jumbo bag building for the old cargo area of the Tuban factory of PT Semen Indonesia (Persero) Tbk with the crashing method. The data used is sourced from observations of project implementation supported by PT. Mahkota Artha Sejati as the contractor. In this case, the crashing method is used by increasing working hours by working overtime on project implementation. The results of this study get optimization results, namely by accelerating project implementation time with cost increases as efficiently as possible, obtained in the implementation of 2 hours of overtime per day. The result is an acceleration of 22 days so that the project duration becomes 128 days, with the project implementation cost increasing by IDR 8,681,402.40. Based on these findings, it can be suggested that, especially in construction projects that experience delays, applying the crashing method is the right solution.